LINGUISTIC FEATURES OF “BOBURNOMA” (Scientific journal of the Fergana State University, 2026)
This article analyzes the linguistic characteristics of “Boburnoma”, written by Zahiriddin Muhammad Babur. It examines the work’s vocabulary, grammatical structures, stylistic elements, as well as its semantic and pragmatic features. The study also highlights the significance of “Boburnoma” in shaping the Uzbek literary language.